(untitled) (The Review of Diabetic Studies, 2025)
Integrated healthcare model (IHM) is a combination of disciplines - radiology, nursing, health information management (HIM), and social services - to provide holistic, patient-centered care. This is a critical analysis that has been carried out based on the literature published in 2020-2024 and evaluates its effectiveness, advantages, and limitations. Integration enhances the accuracy of diagnostic results by ensuring that radiology and nursing collaborate, better data interoperability by making HIM system, and social determinants of health (SDOH) by establishing social services connections. The main results are less readmission (15-25%), and better chronic disease control. Nevertheless, interoperability problems, workforce training and funding silos continue to stand. Examples are used to show the trends in adoption, as well as changes in outcomes. Inequality in implementation is criticized in the discussion, and the recommendations are limited to policy, technology, and training. This model agrees with the Triple Aim yet necessitates systemic changes in the favor of equity and sustainability.